2013
DOI: 10.1111/ijfs.12423
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high‐pressure treatments on microbial loads and physicochemical characteristics during refrigerated storage of raw milk Serra da Estrela cheese samples

Abstract: This work studied the effect of high pressure processing (HPP) at 400, 500 and 600 MPa during 10, 5 and 3 min, respectively, on samples ewe cheese manufactured from raw milk, during storage (100 days) at 5°C. Total aerobic mesophilic and lactic acid bacteria were slightly affected, decreasing by about 1.0 and 0.82 log CFU g À1 , respectively, immediately after HPP treatment at 600 MPa for 3 min, while Enterobacteriaceae, yeasts and moulds, and Listeria innocua were reduced to below the quantification limits. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…Lactobacilli and lactococci (Figure 1A,B) were found at a similar order of magnitude independently of the cheese treatment and packaging system; in Ch C +V cheeses, viable cell numbers were found at 8.37 and 8.29 log cfu g −1 , respectively, at the beginning of storage (0 months), and these remained relatively constant (p ≥ 0.05) throughout the 10 months of storage (exception for lactococci viable cell numbers that increased to 9.30 log cfu g −1 at 3 months of storage (p < 0.05)). Similar values were reported in the literature, never below the 8 log cfu g −1 at 30-60 days of ripening [13,14]. The HPP treatment caused a significant reduction in lactobacilli and lactococci viable cell numbers (p < 0.001) of about 3.8 and 2.5 log cycles, respectively, values close to those previously obtained for Serra da Estrela cheese (450 and 600 MPa/6 min) (submitted data) and in Casar cheese (400 and 600 MPa/5 min) [15].…”
Section: Changes In Microbial Composition Induced By Hpp and Packagin...supporting
confidence: 91%
“…Lactobacilli and lactococci (Figure 1A,B) were found at a similar order of magnitude independently of the cheese treatment and packaging system; in Ch C +V cheeses, viable cell numbers were found at 8.37 and 8.29 log cfu g −1 , respectively, at the beginning of storage (0 months), and these remained relatively constant (p ≥ 0.05) throughout the 10 months of storage (exception for lactococci viable cell numbers that increased to 9.30 log cfu g −1 at 3 months of storage (p < 0.05)). Similar values were reported in the literature, never below the 8 log cfu g −1 at 30-60 days of ripening [13,14]. The HPP treatment caused a significant reduction in lactobacilli and lactococci viable cell numbers (p < 0.001) of about 3.8 and 2.5 log cycles, respectively, values close to those previously obtained for Serra da Estrela cheese (450 and 600 MPa/6 min) (submitted data) and in Casar cheese (400 and 600 MPa/5 min) [15].…”
Section: Changes In Microbial Composition Induced By Hpp and Packagin...supporting
confidence: 91%
“…When high pressure treatment is applied to milk, microbiological quality comparable to that of pasteurized milk can be achieved [ 55 ]. Thus, thermal milk pasteurization can potentially be replaced by HHP treatment for cheesemaking [ 56 ]. However, milk HHP treatments can modify the physico-chemical structure of proteins, causing the fragmentation of casein micelles and denaturation of whey proteins, mainly due to the generation of non-covalent disruptions [ 57 , 58 , 59 ].…”
Section: High Hydrostatic Pressure (Hhp) Processingmentioning
confidence: 99%
“…Medium and long FFA content did not vary with any of the HHP treatments [ 45 , 65 ]. Inácio et al [ 56 ] reported a significant reduction in the microbial count of Enterobacteriaceae , Listeria innocua , molds and yeasts in raw milk ewe’s cheeses treated with high pressure. HHP treatment (400–600 MPa) applied to cheese at 45 ripening days did not significantly modify its physico-chemical characteristics, although lipid oxidation was reduced in comparison with non-pressurized cheeses after 100 ripening days.…”
Section: High Hydrostatic Pressure (Hhp) Processingmentioning
confidence: 99%
“…Like other raw milk cheeses, Serra da Estrela cheese can enable spoilage microorganisms’ growth during ripening and cheese storage. To try avoiding this, a new food processing technology, that is, high pressure processing (HPP), was tested for its efficacy to simultaneously reduce the risk of pathogenic and spoilage microorganisms development without jeopardizing the desired LAB metabolic activity (Inácio, Fidalgo, Santos, Queirós, & Saraiva, ). Serra da Estrela cheese samples with 45 days of ripening were treated at 400–600 MPa pressures during 3–10 min and the effect of HPP after pressure processing and during storage (100 days at 5°C) was studied.…”
Section: Innovation Concerning Serra Da Estrela Cheesementioning
confidence: 99%